Refinement of the pilocarpine-induced status epilepticus model in mice to improve mortality outcomes - Jiang, Mi; Wang, Yu (Frontiers in Neuroscience, 2025)
Systemic pilocarpine administration has been widely implemented to generate rodent models of mesial temporal lobe epilepsy (mTLE), but pilocarpine-induced status epilepticus (SE) in mice causes a high mortality rate, likely due to cardiorespiratory collapse associated with prolonged seizures. Although it has been well known that SE impairs the functional properties of GABARs and benzodiazepine is not effective in treating late SE both in humans and experimental animals, diazepam is still the most commonly used medication to abort SE in pilocarpine-mTLE models. Here, we instead used levetiracetam (LEV), a specific synaptic vesicle protein 2 (SV2) inhibitor in presynaptic terminals, to abort SE and achieved a substantially increased survival rate, providing a robust experimental paradigm to improve animal welfare, research cost, and experimental design. Comparable to previous studies, these mice developed reliable seizures and pathological changes in the hippocampus, including neuronal loss, gliosis, and mossy fiber sprouting. In summary, our optimized LEV-treated, pilocarpine-based protocol establishes a reliable mouse model of mTLE with significantly improved survival outcomes.